Interrogating the scientific and ethical rigor of “kalye” surveys - Cinco, Myrnelle A. (2024)
Access online through this link: https://www.plarideljournal.org/article/interrogating-the-scientific-and-ethical-rigor-of-kalye-surveys
Keywords: Information literacy; Sustainable development; Media literacy; Research ethics; Propaganda